ANTICANCER IMATINIB DELIVERY SYSTEM BASED ON GRAPHENE OXIDE AND OXIDIZED MULTI-WALLED CARBON NANOTUBES: FUNCTIONALIZATION AND TARGETING - Makharza, Eman (An-Najah National University, 2025)
Background: Nanocarriers such as grapheneoxide and oxidized multi-walled carbon nanotubes have attracted attention as drug delivery system vehicles due to their high surface area, low cost, low side effects after modification, and exhibit high dispersibility in physiological media. Also bonding and non-bonding functionalization were considered as a technique for increasing drug binding for being efficient in remediation of cancer cells without effecting normal cells. Objectives: The main objective of this work is to develop a new set of sixteen complexes of functionalized GO and OMWCNTs physically and chemically. Studying the anticancer activity (cytotoxic and cytoststic assays) of each one was assessed. Methodology: The method synthesizing GO and OMWCNTs involves the oxidation of graphite and MWCNTS in the presence of oxidizing agent KMNO4 in acidic media (Hummer's method), then functionalizing GO and OMWCNTs physically and chemically with different compounds (PEGDGE, PEG 400, 1.3-diamino-2-propanol, and - cyclodextrin). Characterization was takes place by FT-IR. Finally, MTT assay by Hela cancer cells and L6 normal cells were studied Results: Some of the newly prepared compounds were characterized by FT-IR to ensure that binding occurs. The functionalization (chemically and physically) and targeting of imatinib with GO and OMWCNTs were validated. Different compounds maximize anti-cancer effectiveness and minimize normal cells toxicity like GO\ OMWCNTs -PEGDGE\ CD\PEG 400 and DAP were noticed. Conclusion: A new novel set of Functionalized GO and OMWCNTs moieties were prepared. Cytotixic and cytostatic assays were done and the formulas GO-PEGDGE\ PEG-400\ DAP and CD physically and chemically functionalized were showed a very promising activities against Hela cancer cells without higher effect on L6 normal cells, this make the compounds possible future drugs for using to treat cancer.
نظام توصيل الإيماتينيب المضاد للسرطان باستخدام الجرافين وأنابيب الكربون المتعددة الجدران المؤكسدة: التعديل الوظيفي والاستهداف